2002
DOI: 10.1021/ic010780s
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical, Spectroscopic, Structural, and Magnetic Characterization of the Reduced and Protonated α-Dawson Anions in [Fe(η5-C5Me5)2]5[HS2Mo18O62]·3HCONMe2·2Et2O and [NBu4]5[HS2Mo18O62]·2H2O1

Abstract: Reaction of excess Fe(cp)(2) (cp = eta(5)-C(5)Me(5)) dissolved in Et(2)O with [NHex(4)](4)[S(2)Mo(18)O(62)] in acetonitrile, followed by recrystallization of the precipitated solid from N,N'-dimethylformamide (DMF), leads to isolation of the complex [Fe(cp)(2)](5)[HS(2)Mo(18)O(62)].3DMF.2Et(2)O. The solid has been characterized by microanalysis, by voltammetric analysis, by (1)H NMR, diffuse reflectance infrared, EPR, and Mössbauer spectroscopies, and by temperature-dependent magnetic susceptibility measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…The major challenge of this approach is the identification of reactive building blocks that can be obtained in solution at concentrations that allow the formation of more complex architectures without undergoing spontaneous rearrangement or isomerisation processes. [17][18][19][20][21][22] Recently, we have identified one facile route that allows the stabilisation of reactive building blocks in solution and indeed resulted in the isolation of novel cluster types in the solid state. Bulky organic cations were used to kinetically stabilise and encapsulate metastable intermediates and prevent further rearrangement into thermodynamically favoured, well-known structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major challenge of this approach is the identification of reactive building blocks that can be obtained in solution at concentrations that allow the formation of more complex architectures without undergoing spontaneous rearrangement or isomerisation processes. [17][18][19][20][21][22] Recently, we have identified one facile route that allows the stabilisation of reactive building blocks in solution and indeed resulted in the isolation of novel cluster types in the solid state. Bulky organic cations were used to kinetically stabilise and encapsulate metastable intermediates and prevent further rearrangement into thermodynamically favoured, well-known structures.…”
Section: Introductionmentioning
confidence: 99%
“…Bulky organic cations were used to kinetically stabilise and encapsulate metastable intermediates and prevent further rearrangement into thermodynamically favoured, well-known structures. [17][18][19][20] By using this approach, a highly charged low-symmetry {Mo 16 10À , was previously isolated. [21] The {Mo 16 } cluster is stable in the solid state and it was shown that the highly negative anion is virtually completely wrapped by the organic counterions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the band at lower energy (ca. 640 nm) is exclusive for 1 and may be ascribed to an intermolecular charge-transfer transition between ferrocenyl donors and POM acceptors [19,21] since none of its constituents exhibit any absorption in this range.…”
Section: Resultsmentioning
confidence: 99%
“…The structural analysis of such compounds has been revealed as a key factor for the identification of potential interesting properties and therefore, an extensive work has been dedicated to the single-crystal structure resolution of compounds combining Fc + or Fc* + units with POM clusters of very different nature. These include fully-oxidized or partially reduced [H x XM 12 O 40 ] n− Keggin-type plenary polyoxomolybdates (X = Si, Ge, P, As; H = 0–1) [14,15,16,17] or –tungstates (X = Si, Fe III ; H = 0–1) [17], first-row transition metal mono-substituted [HPCu(H 2 O)W 11 O 39 ] 4− Keggin or [Cr(OH) 6 Mo 6 O 18 ] 3− Anderson–Evans paramagnetic anions [18] and redox-active [HS 2 Mo 18 O 62 ] 5− Wells–Dawson-type species [19]. Some authors have opted for the organic derivatization of ferrocene units with positively-charged functional groups to lead to ammonium [20] or phosphonium [21] cations that can act as acceptors in the formation of CT salts with Keggin [22] or [M 6 O 19 ] 2− Lindqvist–type POMs (M = Mo, W) [23].…”
Section: Introductionmentioning
confidence: 99%
“…S5), † and then the plot displayed a deviation from linear Curie-Weiss (c ¼ C/(T À q)) behaviour, which was attributed to the temperature independent paramagnetism (TIP) resulting from the polyoxometalate cluster. [23][24][25][26] Interestingly, these two Mo(V) heteropoly blues of two-electron reduction were not magnetic silence at room temperature, but their antiferromagnetic interactions strongly increased with decreasing temperature to full spin antiparallel coupling at 2 K.…”
mentioning
confidence: 99%